Templated synthesis of nickel nanoparticles embedded in a carbon layer within silica capsules. Issue 8 (6th February 2020) - Song, Dandan; Zheng, Jing; Liu, Libin; Alsulami, Hamed; Amin Kutbi, Marwan; Xu, Jingli; Zhang, Min
Abstract : Herein, we have fabricated hollow structured Ni–Pd composites in which a high density of the Ni–Pd NPs are embedded in the carbon layer and also entrapped by SiO2 nanocages. Abstract : The encapsulation of small non-noble metal nanoparticles (NPs) within an inorganic layer has received considerable attention owing to their enhanced stability and high catalytic activity. Using a combination of emulsion-free polymerization, inner RF-Ni 2+ and outer SiO2 coating, and subsequent carbonization treatment, herein, we have fabricated worm-like structured Ni-based composites in which a high density of nickel NPs are embedded in a carbon layer and also entrapped by SiO2 nanocages. We find that the carbonization temperature plays a vital role in adjusting the size of the Ni NPs. A detailed examination of the encapsulated nickel particles synthesized at 700 °C exhibited the best performance on the catalysis of the reduction of 4-NPs. Moreover, owing to the good alloying ability of the Ni NPs with noble metal NPs, the Ni–Pd alloy NPs are also entrapped in the SiO2 nanocages, which exhibit better performance on the catalysis than the Ni-based composites. The encapsulation of Ni–Pd alloys within SiO2 nanocages also improves stability against agglomeration and metal separation during catalytic operation.